Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Since, (x-1)3=8 Therefore, x-1=2 => x=3 Therefore, (x+1)2=(3+1)2=4^2= 16 ans.
0 0 0
Given us (x-1)^3=8, x-1=2, so x=3 nw (x+1)^2=(3+1)^2=16
1 4 1
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts